Hydrogen Peroxide Pretreatment of Palm oil Decanter Cake for Methane Production - ปฐมโรจน์สกุล, เจียระไน; นิยมธูร, อินจิรา; ไชยนันทน์, สิทธิพันธุ์; ไชยนันทน์, สายพิณ; แซ่เตียว, ขวัญจิรา; สารี, ศิริลักษณ์ (Journal of Energy and Environment Technology of Graduate School Siam Technology College, 2019)
Palm oil mill processing industry generate both solid and liquid wasts. Normally, liquid waste is used for producing biogas. wastewater is composed of approximately 14% sludge. Sludge or palm oil mail decanter had little participation in biogas production because it was composed of lignocellulose small role in biogas fermentation because it contains lignocellulose which was difficult to degrade by microorganisms. Therefore, pretreatment of this decanter cake for enabling microbial degradation is necessary before biogas processing. The research was aimed to study the optimul conditions for pretreatment necessary before biogas processing. This research was aimed at studying the optimal The optimum condition for pretreatment of palm oil mill liqid waste (14% decanter cake) by using hydrogen peroxide 2,000 ppm, and the ratio of hydrogen peroxide and ferrous sulfate (catalyst) at 10: 1. The reaction was performed at 50 c for 20 min. After hydrogen peroxide pretreatment, the Reducing sugar was released to the solution at 974.5 + 1.5 ug/ml, And COD was decreased from 28,200 to 27,600 mg/L. When comparing biogas production between non protreated, and pretreated liquid waste, biogas from the prerteated waste had methane up 0.406 m ch/kgCOD. whihe non-reconditioned waste had Only 0.028 mCH/kgCOD. The methane production increased by 14.5 times.